For the Love of Shirley One Woman's Challenges and Choices in Postwar Jewish America - Baumel-Schwartz, Judith Tydor; Baumel-Schwartz, Judith Tydor (Peter Lang, 2020)
This is the story of Shirley Rosalyn Kraus Tydor, the American-born daughter of early 20th-century Jewish immigrants from Eastern Europe. Her father was an atheist\communist and her mother a traditional Jew. Shirley, the rebel, became a career woman and married her boss, an Orthodox Holocaust survivor and a widower twice her age, with two adult children. The couple lived in South Dakota and Montana, returned to NY in 1959 where their daughter was born, and worked as travel agents before moving to Israel in 1974. Shirley traveled the world when few Americans even possessed passports. "For the Love of Shirley" provides readers with an intimate glimpse into one Jewish woman's challenges and choices in postwar Jewish America